PELATIHAN PENGELOLAAN KEUANGAN DAN ORGANISASI NIRLABA SEBAGAI UPAYA OPTIMALISASI GOOD CORPORATE GOVERNANCE PADA GOOD VILLAGE PROJECT - Sari, Arista Fauzi Kartika; Efendi, Erfan (LPPM Universitas Flores, 2025)
The purpose of this community service activity is to provide training to a non-profit organization, namely the Good Village Project, on non-profit corporate governance from the aspect of financial management, including financial literacy and accounting information systems and non-profit organization management. This activity is carried out in four stages: preparation of community service materials, implementation of community service activities on financial literacy in theory and practice, in preparation of financial reports using financial information systems. Managerial assistance and evaluation through several tests to assess the effectiveness of the community service activities that have been carried out. This activity received a very good response from the participants, based on the evaluation questionnaire given to participants, with an average value of more than 4 on a scale of 1-5, which means that participants assessed this community service activity with the criteria of